The Resilience of Traditional Indonesian Architecture: A Review of Existing Research - I Gusti Ngurah Antaryama; Audrey Tara Dianagri (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2026)
The rapid rise of modern lifestyles and technologies, along with disturbances to natural imbalances, has threatened the resilience of traditional architecture worldwide, including Indonesia. While some communities embrace modern structures as symbols of contemporary life, others adapt traditional buildings to changing needs while maintaining cultural identity. This study examines the resilience of Indonesian traditional architecture through a systematic review of 40 cases taken from existing research articles. It applies a resilience framework for the data analysis to reveal the extent to which the architecture responds to current changes and imbalances. Findings show two tendencies: modernisation drives changes in materials, layouts, and functions, while enduring connections to climate, spatial logic, and cultural principles. Adaptations range from substantial modifications that retain structural and functional integrity to superficial applications of traditional ornamentation on modernised buildings. Although a few cases fail to adapt, most demonstrate adaptive resilience, maintaining both function and cultural meaning.